To solve the polynomial equation \( x^4 - 11x^2 + 10 = 0 \) using factoring and the root method, we can start by performing a substitution. Let \( y = x^2 \). This transforms the original equation into a quadratic equation in terms of \( y \):
\[ y^2 - 11y + 10 = 0 \]
Next, we can factor the quadratic:
\[ (y - 1)(y - 10) = 0 \]
Setting each factor equal to zero gives us:
\[ y - 1 = 0 \quad \text{or} \quad y - 10 = 0 \]
This results in:
\[ y = 1 \quad \text{or} \quad y = 10 \]
Now we will substitute back for \( x \):
-
For \( y = 1 \): \[ x^2 = 1 \] Taking the square root of both sides, we get: \[ x = \pm 1 \]
-
For \( y = 10 \): \[ x^2 = 10 \] Taking the square root of both sides, we get: \[ x = \pm \sqrt{10} \]
Combining all the solutions, we have:
\[ x = 1, -1, \sqrt{10}, -\sqrt{10} \]
Thus, the complete solution set is:
\[ \boxed{1, -1, \sqrt{10}, -\sqrt{10}} \]